Serological insights and clinical patterns of dengue fever in a tertiary care hospital: a survey-based study (Journal of Ideas in Health, 2025)
Background: Dengue fever, a vector-borne disease caused by the dengue virus (DENV) and transmitted by Aedes mosquitoes, remains a public health concern in India, especially due to its seasonal and geographical variability. The disease manifests with symptoms like fever, myalgia, rashes, leukopenia, and thrombocytopenia, affecting various organs. This study aimed to examine the demographic patterns, clinical presentations, and healthcare-seeking behavior of paediatric dengue patients. Additionally, it analyzed dengue positivity trends from 2021 to 2023.Methods: A descriptive cross-sectional study was conducted from September to December 2021 among suspected dengue paediatric patients admitted to the Paediatrics department of Autonomous State Medical College Firozabad. Diagnostic tests included Dengue rapid NS1, ELISA NS1 Antigen, and IgM ELISA. Data were analyzed to assess clinical symptoms, healthcare access, and yearly dengue trends.Results: A total of 6,445 patients were clinically suspected of dengue at the Paediatrics IPD, Autonomous State Medical College, Firozabad, Uttar Pradesh. Among them, 386 were confirmed dengue-positive by rapid card, NS1 antigen, or IgM ELISA tests. The highest number of suspected cases (43.17%) was observed in school-going children (6–12 years). Males (55.47%) were more affected than females (44.53%), with nearly equal distribution between rural and urban areas. Platelet counts varied widely, with 31.73% having counts between 50,000–100,000. Fever with myalgia (75.65%) was the most common symptom. Dengue positivity fluctuated across years, with the highest rate in 2021 (193/1147 cases), followed by declines in 2022 and 2023.Conclusion: Dengue fever shows a variable trend in incidence, with significant impact from healthcare access and public awareness. Improving awareness and timely diagnosis could help mitigate the severity of cases in future outbreaks.
Keywords: Dengue, Paediatric Case, ELISA, Clinical Manifestation, Positivity Trends, India